Penerapan Pendidikan Kesehatan Keluarga Tentang Bahaya Asap Rokok Dalam Pencegahan ISPA Pada Balita: Studi Kasus - Ramanda Setiawan; Resmi Pangaribuan; Ade Irma Khairani (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Acute respiratory infection (ARI) is one of the diseases that most often attacks toddlers, especially aged 1-4 years. One of the main risk factors for ARI is exposure to cigarette smoke in the home environment. Health education regarding the dangers of smoking is an important step in increasing family awareness to create a healthy environment for toddlers. This research aims to provide health education to families regarding the dangers of smoking on the incidence of ARI in toddlers. This research method is descriptive with a case study approach to family nursing care which includes assessment, diagnosis, intervention, implementation and evaluation. The research was conducted on 2 family respondents who had toddlers aged 1-4 years who lived at home with active smokers. This research was conducted in the work area of ​​the Medan Deli Community Health Center for 1 week with 3 meetings. The instruments used include family assessment formats, questionnaires, and leaflet media. Research results show that there is an increase in family knowledge and awareness after being given health education. Families begin to limit smoking activities at home, open ventilation regularly, and understand the risk of ARI due to exposure to cigarette smoke. Both respondents stated that they had started making rules not to smoke near children. Analysis of the results shows that health education is effective in increasing family awareness of the dangers of smoking which can cause ARI in toddlers. Conclusions and suggestions: Health education given gradually and repeatedly for 1 week can increase family knowledge and attitudes in preventing ISPA in toddlers due to exposure to cigarette smoke. It is hoped that families can continue to maintain this healthy behavior to support optimal growth and development of toddlers.